Effects of eicosapentaenoic acid on hepatic dyslipidemia and oxidative stress in high fat diet-induced steatosis. (August 2015) - Hirotani, Yoshihiko; Ozaki, Nozomi; Tsuji, Yoshihiro; Urashima, Yoko; Myotoku, Michiaki
Abstract We investigated the ability of eicosapentaenoic acid (EPA) to prevent high-fat diet (HFD)-induced obesity and non-alcoholic fatty liver disease (NAFLD). Male C57BL/6J mice were fed standard chow (5.3% fat content), an HFD (32.0% fat content) or an HFD + EPA (1 g/kg/day EPA for the last 6 weeks) for 12 weeks. Serum total cholesterol, hepatic triglyceride and total cholesterol levels were significantly increased in the HFD group, in comparison with those of normal mice (p < 0.01). In contrast, hepatic triglyceride and total cholesterol levels were significantly decreased in the HFD + EPA group, in comparison with those of the HFD group (p < 0.05). In addition, EPA decreased the body weight of obese mice and improved hepatic function. Hepatic superoxide dismutase activity and glutathione levels were significantly decreased in obese mice, but increased with EPA administration. Our data suggest that EPA supplementation has a beneficial effect on NAFLD progression.